Sukuk as a Model for Infrastructure Financing Published by BUMN Companies - Rahmayati M.E.I (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
Abstract. This study aims to offer a new model in terms of financing infrastructure development in Indonesia through Sukuk that is adjusted based on the purpose of its use and type of infrastructure, by using the Musharaka Mutanaqishah (MMQ) contract, by BUMN companies and then offering the Sukuk to pension fund companies. This is as an alternative investment for pension fund companies to get profit sharing that benefits from the rate of return for the sukuk. The methodology in this study uses a systems thinking approach with secondary data collection techniques obtained from supporting literature. The results of this study that the non-bank financial industry in Indonesia is very important for infrastructure development, that is by using pension funds where the instrument is sukuk using the Musharaka Muqtanaqishah (MMQ) contract.